2008
DOI: 10.1364/ol.33.002128
|View full text |Cite
|
Sign up to set email alerts
|

Extended phase matching of high harmonics driven by mid-infrared light

Abstract: We demonstrate that phase-matched frequency upconversion of ultrafast laser light can be extended to shorter wavelengths by using longer driving laser wavelengths. Experimentally, we show that the phase-matching cutoff for harmonic generation in argon increases from 45 to 100 eV when the driving laser wavelength is increased from 0.8 to 1.3 microm. Phase matching is also obtained at higher pressures using a longer-wavelength driving laser, mitigating the unfavorable scaling of the single-atom response. Theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
110
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(113 citation statements)
references
References 13 publications
0
110
0
Order By: Relevance
“…Since the energetics of this strong-field process is governed by the ponderomotive energy U p of a tunnel-ionized electron in a laser field (where U p ∝ λ 2 ), increasing the laser wavelength λ opens the way for producing higher-energy photons and electrons in strong-field reactions. For high-order-harmonic generation (HHG), such long-wavelength laser sources allow experimentalists to utilize higher-pressure gas targets and to extend phase-matching conditions into the x-ray regime, thus enabling the production of a nearly continuous spectrum of high-order harmonics having extremely short wavelengths [4][5][6][7][8][9]. As the wavelength increases, these beneficial macroscopic features of the target medium for phase matching compete with the negative feature of the microscopic singleatom HHG yield, which decreases rapidly [1,10].…”
Section: Introductionmentioning
confidence: 99%
“…Since the energetics of this strong-field process is governed by the ponderomotive energy U p of a tunnel-ionized electron in a laser field (where U p ∝ λ 2 ), increasing the laser wavelength λ opens the way for producing higher-energy photons and electrons in strong-field reactions. For high-order-harmonic generation (HHG), such long-wavelength laser sources allow experimentalists to utilize higher-pressure gas targets and to extend phase-matching conditions into the x-ray regime, thus enabling the production of a nearly continuous spectrum of high-order harmonics having extremely short wavelengths [4][5][6][7][8][9]. As the wavelength increases, these beneficial macroscopic features of the target medium for phase matching compete with the negative feature of the microscopic singleatom HHG yield, which decreases rapidly [1,10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of phase-matching in capillaries have either included the radial variation of ionization through radial averaging [12][13][14], allowing no variation of the phase-matching conditions with radius, or have used numerical propagation codes to model the buildup of the harmonic field [15,16]. Recently it has been demonstrated that phase-matching can be extended to the water-window region harmonics using a mid-infrared driving laser [17,18]. It has also been noted that the temporal variation of phase-matching conditions is crucial in determining the output from HHG experiments [19][20][21][22], however none of this work has taken into account the spatially varying phasematching conditions found in waveguide HHG.…”
Section: Introductionmentioning
confidence: 99%
“…The second one is based on the control of macroscopic properties of the target samples (i.e. phase matching) leading to very ingenious target geometries [16][17][18]. However, all these approaches rely on detecting the far-field properties of the harmonic yield which is a consequence of collective single emitter's ones.…”
mentioning
confidence: 99%